Туристу о растениях - Мацюцкий Степан Петрович (Мир туристских интересов, 1988)
Экземпляры: ЧЗ (20181012) / Инвентарный номер: 21182 / Цена: 0.50 / Сис.шифр: 28.5 / Авт.знак: М 36 / ГРНТИ: 34 / ББК: 28.5